O rock progressivo depois de 1990 - Moraes, Carlos Henrique Rodrigues de (2018)
This research develops reflections and analyses around the music and history of Progressive Rock. Drafting a historical and musical profile as an objective, this work contemplated a description of its origins, its most notable characteristics, and how it progressed up until current days. The work is focused on the activity of new bands from 1990s onwards. The research analyzed, in a descriptive manner, the career and music from some of the bands that had a considerable impact on Progressive Rock and its community, over the fixated period, also tracing comparisons between this new music and the works of other influential artists in this subgenre on previous decades.